Aging and biliary tract cancers: Epidemiology, molecular biology, and clinical practice. Issue 2 (13th June 2022) - Weng, Xiaoling; Song, Xiaoling; Shao, Rong; Liu, Fatao; Liu, Yingbin
Abstract : Abstract: Biliary tract cancer (BTC) that contains cholangiocarcinoma, gallbladder cancer, and ampullary cancer is highly malignant and mostly diagnosed in elderly patients. Over the past decades, human life has globally risen; thus, aging emerges as the primary risk factor for BTC. However, an effective treatment for this vulnerable population remains a large clinical challenge. As a result, the incidence and mortality of TBC remains high. Here, we discuss the potential link between aging and BTC from the aspects of molecular and cellular mechanisms, surgical resection, and chemotherapy. In addition, we update a number of clinical trials that are currently ongoing in elderly patients. The overview of BTC in elderly patients is expected to help develop a new therapeutic strategy tailored to this elderly population, ultimately improving their life quality. Abstract : This is a review on the effects of aging on biliary tract cancer (BTC). We discuss the potential link between aging and BTC from the aspects of molecular mechanisms (including the DNA damage repair (DDR), cell senescence and the tumour microenvironment (TME)) and clinical challenges.